The process of counseling and therapy - Moursund, Janet (Prentice Hall, 2002)
"This is a book that clearly and skillfully integrates most theories of psychotherapy ... using frequent references to literature ... and direct quotations, which substantiate [their] position on specific issues." - Senez Rodriquez-Charbonier, Ph.D., Grand Valley State University